The effects of zinc sulfate mineral supplementation on Achilles tendon healing in rats - Onaloglu, Yigit; Alagoz, Ender; Solmaz, Mahsum; Erdogan, Nilsen Yildirim; Demirkol, Metehan; Kucukyildirim, Bedri Onur (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2024)
BACKGROUND: The Achilles tendon is the most commonly injured and ruptured tendon in the body and typically occurs during participation in sports or recreational activities in men between 30 and 50 years of age. Treatment options for Achilles tendon rupture include conservative and surgical approaches. Conservative treatment is associated with a higher risk of rerupture, while surgical treatment carries a risk of wound site complications. Generally, both methods result in a prolonged tendon healing time. Studies are ongoing to identify biomolecules that aid tendon repair. The main objective of our study is to investigate the effects of zinc sulfate METHODS: Forty-eight female Sprague-Dawley rats were divided into four equal groups (C-15, C-30, ZnSO4-15, and ZnSO4-30) after standard Achilles tendon repair surgery. The ZnSO4-15 and ZnSO4-30 groups received an oral zinc sulfate monohydrate solution (50 mg/kg/day) for 15 and 30 days, respectively. The C-15 and C-30 groups were given 1 mL of distilled water per day orally during the experimental periods. Rats were sacrificed on the 15th and 30th day depending on their groups, and the healing of the operated tendons was evaluated using Movin and Bonar histopathologic scoring. For biomechanical analyses, the operated and intact Achilles tendons of all groups were removed, and tensile tests were performed to determine the tensile strength and toughness values for each tendon. RESULTS: Movin and Bonar scores were significantly lower in the ZnSO4-15 group than in the C-15 group and in the ZnSO4-30 group than in the C-30 group (p<0.05). Although we did not find the biomechanical results statistically significant, the intact tendons of the ZnSO4-15 group exhibited higher toughness than those of the C-15 group, and the tensile strength and toughness values of the operated and intact tendons of the ZnSO4-30 group were also higher than those of the C-30 group. CONCLUSION: Zinc sulfate monohydrate mineral supplementation had histopathologically positive effects on the proliferation and remodeling stages of Achilles tendon healing and may biomechanically benefit both operated and intact tendons.
Keywords: Achilles tendon healing; biomechanical examination; Experimental study; histopathological examination zinc sulfate; mineral supplementation; METALLOTHIONEIN; TENDINOPATHY; ANTIOXIDANT; PATHOLOGY; OXIDE; MODEL; Emergency Medicine